EVALUASI PASCADIKLAT PENGAWAS OPERASIONAL PERTAMBANGAN MINERAL DAN BATUBARA TINGKAT PERTAMA TERHADAP PERUBAHAN PERILAKU ALUMNI PT TIMAH TBK. - Revi Timora Salajar; Imelda Hutabarat (PPSDM Geominerba, 2019)
The need for a large number of competent mining operations supervisors at PT Timah Tbk. is very much needed until now. This is an embodiment of fulfilling the mandate in the Minister of Energy and Mineral Resources Regulation No. 26 of 2018 concerning the Implementation of Good Mining Engineering Rules, Article 7, “every mining business licence must have the competent mining technical personnel in accordance with the provisions of laws and regulations”. As a result of these regulations, PT Timah Tbk seeks to include its employees in the Training and Certification of the First Operational Supervisor at PPSDM Geominerba. This post-training evaluation was carried out at PT Timah, Tbk. Located in Sungailiat City, Bangka Belitung Province. The results of the post-training evaluation specifically found that the practice time was considered to be insufficient. They hope that there will be field observations to implement training courses for conducting inspections. In addition, the duration of mining safety analysis needs to be added.